Development of Interactive Learning Media Using Hyperlink PowerPoint to Enhance Arabic Writing Skill - Sholihah, Faizatun; El Warfali, Suliman H Suliman; B. Smeer, Zeid (Abjadia : International Journal of Education, 2025)
This study develops interactive learning media using Hyperlink PowerPoint—an interactive presentation format in which slides are interconnected through clickable links—to enhance students’ Arabic writing skills. The media also integrates the Trigger feature to enable dynamic slide responses and non-linear navigation. Employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research was conducted with 30 tenth-grade students at MA Mu’allimin NWDI Pancor. Data were collected through expert validation, teacher and student questionnaires, and pre-test/post-test assessments. The learning objectives targeted after the media development included: (1) enabling students to construct grammatically correct simple sentences with accurate subject–predicate–object order, (2) enabling students to create simple sentences using relevant vocabulary, and (3) enabling students to compose two to three coherent and logical sentences based on the themes Al-Hayat al-Yaumiyyah and Al-Hiwayah. Validation results showed scores of 80% from the media expert (“valid”) and 85% from the material expert (“very valid”). Practicality scores were 84% (“very practical”) from teachers and 80% (“practical”) from students. Paired sample t-test results indicated a significant improvement in students’ writing performance (t = 26.840, p < 0.001), particularly in syntactic accuracy, vocabulary usage, and text coherence. The interactive features of Hyperlink PowerPoint, supported by the Trigger function, foster active engagement, support self-paced learning, and can be adapted to various topics in Arabic writing instruction. This study concludes that Hyperlink PowerPoint is a valid, practical, and effective tool for developing students’ Arabic writing skills and serves as an innovative resource for Arabic language learning.